Evaluasi Kesuksesan E-Plantation Menggunakan Model DeLone dan McLean di PT Alam Permai Makmur Raya - Sherly Silviani; Joy Nashar Utama Jaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
PT. Alam Permai Makmur Raya is one of the palm oil companies that has implemented E-Plantation in its business processes but it has never been evaluated before, so researchers are interested in evaluating E-Plantation to determine the success of the system. This study adopted the DeLone and McLean model covering 6 variables,namely, system quality, information quality, service quality, use, user satisfaction and net benefit which are processed using SmartPLS. This study aims to test 8 research hypotheses and find out what factors most influence their success. The results showed that there were 5 accepted hypotheses and 3 rejected hypotheses. E-Plantation cannot be said to be completely successful because there is no influence of system quality on user use and satisfaction and no influence of user satisfaction on net benefits. There are two variables that have a major influence on the success of E-Plantation, namely, the service quality variable with a T-Statistic of 3.779 and the usage variable of 4.441 so that it can be interpreted that the service quality of E-Plantation is good so that users are active to use this system.